Hotel Reservation System Using Daily Language to Optimize the Hotel Occupancy - Sulistyanto, Hernawan; Nurgiyatna, N (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Hotel occupancy leveling is one of crucial components in the hotel revenue management. Revenue management is meant to maximize the revenue management from various limited supplies. There has been a trend that the prevailing hotels nowadays have improved the technology aspect to increase the hotel quality and eventually the hotel occupancy. The modeling for hotel occupancy representation is a complex problem because the presentation has linked with the other processes, such as: the arrival reservation, cancelation, length of stay, no-show, group reservation, seasonality, and so on. In fact, the problems rising up recently are not limited on the workers or capital, but more in providing the reservation information. The information should give facility by providing simple method of reservation for the customers. This paper provided brief explanation regarding with the hotel occupancy and then explored the reservation system which implemented Indonesian language called Humane Reservation Assistance (HuResTan). Obvious contribution of this application was the implementation of Indonesian language in the reservation process. Furthermore, it provided the preference to make a reservation for the hotel room after the searching result for targeted room was completed.